Military Families' Perceptions of Neighborhood Characteristics Affecting Reintegration: Development of an Aggregate Measure. (2nd January 2017) - Beehler, Sarah; Ahern, Jennifer; Balmer, Brandi; Kuhlman, Jennifer
ABSTRACT: This pilot study evaluated the validity and reliability of an Experience of Neighborhood (EON) measure developed to assess neighborhood characteristics that shape reintegration opportunities for returning service members and their families. A total of 91 post-9/11 veterans and spouses completed a survey administered at the Minnesota State Fair. Participants self-reported on their reintegration status (veterans), social functioning (spouses), social support, and mental health. EON factor structure, internal consistency reliability, and validity (discriminant, content, criterion) were analyzed. The EON measure showed adequate reliability, discriminant validity, and content validity. More work is needed to assess criterion validity because EON scores were not correlated with scores on a Census-based index used to measure quality of military neighborhoods. The EON may be useful in assessing broad local factors influencing health among returning veterans and spouses. More research is needed to understand geographic variation in neighborhood conditions and how those affect reintegration and mental health for military families.